Properties of holographically produced complex spatial filters for real-time deconvolution of blurred ultrasound images - SOMER, Jan; JONGSMA, Frans (Archives of Acoustics, 1984)
All ultrasound pulse-echo imaging systems suffer from limitations of both lateral and axial resolution due to beam-width and pulse-length respectively. Therefore a point-target will always be depicted as a blurred dot. In essence only deconvolution of the system’s impulse-response (or smear-function or blurring) could provide further improvement. Earlier an optical system was described potentially capable to process the echo-signals as received by a phased-array pulse-echo system in real-time and in two dimensions. A holographic method can be used to produce a complex spatial filter for a particular reference-target which performs to some extent inverse filtering or deconvolution. Both model-evaluations and experiments were carried out, showing a reasonable agreement. With the used amplitude transmission-characteristic of the photographic emulsion complex spatial filters can be produced showing inverse-filter properties For only a small dynamic range. Further work should be devoted to increasing the filter’s dynamic range and dynamic range compression methods prior to the filtering.